Intimacy in Non-Western Discourses of Terrorism: An Analysis of Three Bollywood Films. Issue 2 (3rd July 2018) - Devadoss, Christabel; Cromley, Gordon
Abstract : The role of terrorism and the War on Terror have become increasingly prominent within political climates. As research into social media and mass media has grown with the ability to leverage Internet-based resources, this article approaches the increased security climate in the United States and Islamophobia through film analysis of non-Western films. Geographies of film have been well developed within the context of geopolitics, but less so in the analysis of non-Western film industries such as Bollywood. We argue that non-Western film analysis is crucial to understanding changing political climates and challenges the lines between representation and the everyday. We focus on three films in the world's biggest film industry to analyze intimacy and the role of the body within discourse in film. Using 11 September 2001 (9/11) as a point of comparison, we examine the intimate portrayal of terrorism in Bollywood films in both pre-9/11 and post-9/11 contexts. We highlight Bollywood's critique of U.S. antiterrorist tactics post-9/11 and expose anti-Muslim sentiments reinforced in Hollywood films. We also suggest that because the United States is an increasingly diverse country, non-Western media are becoming increasingly important, especially in an era that silences certain groups and media.